Multimodal neuroimaging relationships in progressive supranuclear palsy. (September 2019) - Sintini, Irene; Schwarz, Christopher G.; Senjem, Matthew L.; Reid, Robert I.; Botha, Hugo; Ali, Farwa; Ahlskog, J. Eric; Jack, Clifford R.; Lowe, Val J.; Josephs, Keith A.; Whitwell, Jennifer L.
Abstract: Progressive supranuclear palsy is characterized primarily by 4R tau inclusions, atrophy in the brainstem and basal ganglia, and neurodegeneration along the dentatorubrothalamic tract, which are measurable in vivo using flortaucipir PET, T1-weighted MRI, and MRI with diffusion tensor imaging (DTI). However, little is known about how these processes relate to each other. The aim of this study was to investigate multimodal associations between flortaucipir PET uptake, tissue volume loss on structural MRI and white matter tract disruption on DTI. Thirty-four patients with progressive supranuclear palsy and 29 normal controls underwent flortaucipir PET, MRI and DTI. Voxel-wise comparison was performed between patients and controls. Sparse canonical correlations analysis was applied on regional measurements of flortaucipir uptake, tissue volume, fractional anisotropy and mean diffusivity of the PSP population. Pearson's correlation coefficients were assessed across modalities on the regions identified by the sparse canonical correlation analyses. Sparse canonical correlation analyses identified associations between elevated flortaucipir uptake in the cerebellar dentate, red nucleus and subthalamic nucleus and decreased volume in the same regions, and decreased fractional anisotropy and increased mean diffusivity in tracts including the superior cerebellar peduncle, sagittal striatum and posterior corona radiata. Furthermore, decreased fractional anisotropy and increased mean diffusivity in the body of the corpus callosum and anterior and superior corona radiata were related to volume loss in the frontal lobe. Tau uptake measured by flortaucipir PET appears to be related to the neurodegenerative process of progressive supranuclear palsy, including reduced tissue volume and white matter tract degeneration. Highlights: Atrophy, white matter tract degeneration and flortaucipir uptake are related in PSP. Cerebellar dentate and brainstem flortaucipir uptake is related to local atrophy. Flortaucipir uptake is related to distal white matter tract degeneration. White matter tract degeneration is associated to frontal volume loss. Flortaucipir PET uptake appears to be related to the PSP neurodegenerative process.